2001
DOI: 10.1055/s-2001-17730
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sheep Grazing on Net Nitrogen Mineralization Rate in Two Temperate Salt Marshes

Abstract: Nitrogen mineralization rate was studied in grazing trials with three different stocking rates (0, 3, 10 sheep ha‐1) in two man‐made salt marshes, viz. a Puccinellia maritima‐dominated low salt marsh and a high salt marsh dominated by Festuca rubra. Mineralization rates were derived from the amounts of mineral N which accumulated in situ during six‐week incubation periods in tubes containing undisturbed soil cores from the upper 10 cm soil layer. The annual rates of net N mineralization were significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…Inorganic nitrogen showed higher contents in wetland soils during spring and early summer before water and sediment regulation, except for the tidal flooding wetland which might be greatly affected by tidal fluctuation. During this period, labile C and N were easily available from overwinter decomposition with increasing temperature 29. Then the inorganic N decreased after June because nitrogen was probably incorporated in plant biomass and immobilized by soil microbial biomass 30.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic nitrogen showed higher contents in wetland soils during spring and early summer before water and sediment regulation, except for the tidal flooding wetland which might be greatly affected by tidal fluctuation. During this period, labile C and N were easily available from overwinter decomposition with increasing temperature 29. Then the inorganic N decreased after June because nitrogen was probably incorporated in plant biomass and immobilized by soil microbial biomass 30.…”
Section: Discussionmentioning
confidence: 99%
“…Consequences of these activities include the incorporation into the lake basin of large amounts of agricultural soil, drained from ploughed fields during the rainy periods, concentration of fertilizers or pesticides in the lake, washed from adjacent treated fields, direct changes in soil structure as sheep step on the salt shores (Fig. 13e), and nitrification and vegetation changes by sheep activity (Kiehl et al 2001, Knisley 2011). Trails and dirt roads are used traditionally by agricultural vehicles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Trampling by livestock leads to compaction of the soil and, thus, decreased accretion (e.g. Kiehl et al 2001;Schrama et al 2013). Several studies have shown that defoliation alters vegetation composition and positively affects soil salinity (e.g.…”
Section: Salinization and Managementmentioning
confidence: 99%